2016
DOI: 10.1590/0102-6720201600010010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Deficient Nutrition in Bone Mass After Bariatric Surgery

Abstract: Background: Essential nutrients are considered for the prevention of the bone loss that occurs after bariatric surgery. Aim: Evaluate nutrients involved in bone metabolism, and relate to serum concentrations of calcium, vitamin D, and parathyroid hormone, and the use of supplements and sun exposure on the bone mass of patients who had undergone gastric bypass surgery. Methods: An observational study, with patients who had undergone the surgery 12 or more months previously, operated group (OG), compared to a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 34 publications
1
18
2
1
Order By: Relevance
“…Studies previously demonstrated that there is a reduction on the skeletal muscle mass and bone mass through the years after the bariatric surgery. This fact may cause complications such as the decrease of the daily energy expenditure and impacts on the bone metabolism 5 , 8 , 31 , and consequently a decrease of the physical activity indexes; however, this last influence was not observed in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…Studies previously demonstrated that there is a reduction on the skeletal muscle mass and bone mass through the years after the bariatric surgery. This fact may cause complications such as the decrease of the daily energy expenditure and impacts on the bone metabolism 5 , 8 , 31 , and consequently a decrease of the physical activity indexes; however, this last influence was not observed in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…Regardless of the metabolic benefits stemming from gastric bypass 5 , many studies 11,14,19,26,27,31 have reported the impact of nutritional deficiencies after gastric bypass, including its effects on bone metabolism 1 , 4 , 7 , 8 , 10 , 17 , 18 , 22 , 28 , 30 , 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery could impact bone metabolism and induce significant changes, such as decreased mechanical loading, calcium/vitamin D malabsorption with secondary hyperparathyroidism, nutritional deprivations, changes in fat mass and alterations in fat- and gut-derived hormones[ 25 - 27 ].…”
Section: Nutritional Issues After Bariatric Surgerymentioning
confidence: 99%